Economics : and contemporary issues - Edgmand, Michael R.; Moomaw, Ronald L.; Olson, Kent W. (Fort Worth : Dryden Press, 1998)
Economics
Keywords: Economics; Economic systems; Market; Poverty; Macroeconomy; Unemployment; Inflation; Economic growth; World economy